2020
DOI: 10.1177/2042018820925326
|View full text |Cite
|
Sign up to set email alerts
|

Moderate intensity exercise in hypoxia increases IGF-1 bioavailability and serum irisin in individuals with type 1 diabetes

Abstract: Aim: This study aimed to determine the effect of moderate intensity continuous exercise (Ex) and hypoxia (Hyp) on serum brain-derived neurotrophic factor (BDNF), insulin-like growth factor-1 (IGF-1) and its binding protein-3 (IGFBP-3), irisin and cytokines levels in patients with type 1 diabetes (T1D). Methods: A total of 14 individuals with T1D (age: 28.7 ± 7.3 years) and 14 healthy adults (age: 27.1 ± 3.9 years) performed 40-min continuous Ex at moderate intensity (50% lactate threshold) on a cycle ergometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Nevertheless, it has been shown that hypoxia promotes lowering of blood glucose levels through the stimulating effect of HIF-1 on glycolysis and as a result of the increased expression of GLUT4 glucose transporters in muscle tissue independently of muscle work [ 13 ]. In one of the few studies in patients with type 1 diabetes, a single 40 min moderate-intensity exercise bout (50% of lactate threshold) on a cycloergometer in hypoxia was associated with a reduction in glycemia immediately after training and within 24 h of recovery compared to the same effort under normoxic conditions [ 11 ]. Regardless of the conditions in which the training took place, it was a moderate effort that usually led to lowering of glycemia in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it has been shown that hypoxia promotes lowering of blood glucose levels through the stimulating effect of HIF-1 on glycolysis and as a result of the increased expression of GLUT4 glucose transporters in muscle tissue independently of muscle work [ 13 ]. In one of the few studies in patients with type 1 diabetes, a single 40 min moderate-intensity exercise bout (50% of lactate threshold) on a cycloergometer in hypoxia was associated with a reduction in glycemia immediately after training and within 24 h of recovery compared to the same effort under normoxic conditions [ 11 ]. Regardless of the conditions in which the training took place, it was a moderate effort that usually led to lowering of glycemia in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with type 1 diabetes have decreased IGF-1 expression which leads to disturbances in bone metabolism and neuropathy, as well as muscle atrophy and cardiovascular complications. It has been shown that physical exercise performed in conditions of moderate hypoxia (2500 m above sea level) leads to an increase in the concentration of free IGF-1 [ 11 ]. Exercise in hypoxia also increases NO production and lowers the concentration of pro-inflammatory TNF-alpha.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is a lack of evidence regarding hypoxic exercise induced AT browning in human participants. However, studies have reported weight loss effects of hypoxic exercise, as well as its inducing WAT browning capabilities in rats, particularly with the upregulation of Irisin and Leptin levels, adipokines associated with AT browning by promoting adipose tissue transdifferentiation into beige adipose tissue as well as direct activation of WAT lipolysis and fatty acid oxidation [29][30][31][32][33]. Moreover, studies exploring the effects of hypoxic physical activity (PA) were usually replicated in a hypobaric environment using chambers or conducting studies in mid-mountain areas, which poses risks and limitations like organ structural changes, that can lead to collapse and fainting, as well as economic and technical difficulties [34].…”
Section: Exercise-induced Browningmentioning
confidence: 99%
“…However, there are relatively few studies on the browning of WAT by exercise under hypoxic conditions. One study [ 61 ] examined the adipose tissue changes in patients with type 1 diabetes after moderate intensity (50% lactate threshold, 40 min) exercise under normoxia or hypoxia. It was found that the serum irisin level was higher after exercise under hypoxia than under normal oxygen.…”
Section: Effects Of Different Exercise Programs On Promoting the Browning Of Watmentioning
confidence: 99%